The power of community-based participatory research: Ethical and effective ways of researching. Issue 1 (1st January 2022) - F. Amauchi, Juliana F.; Gauthier, Maeva; Ghezeljeh, Abdolzaher; L. Giatti, Leandro L.; Keats, Katlyn; Sholanke, Dare; Zachari, Danae; Gutberlet, Jutta
ABSTRACT: In this article we explore ethical and effective standards of Community-Based Participatory Research (CBPR) as a practice that differentiates itself from conventional research. We emphasize the fundamental and active role of community in participatory processes by legitimizing multiple forms of knowledge through a variety of methods that together provide discovery and dissemination of the findings. The goal of CBPR is to directly or indirectly achieve social transformation and social/ environmental justice. Researchers and community participants equally share control over the research, results and outputs. We present three case studies, highlighting some of the ethical concerns and difficulties encountered in the research process and speak to the implementation of key principles that sustain CBPR. The research follows a "slow" praxis, with relationship building and learning about local contexts, offering diverse ways of involving community, using innovative tools and approaches. Finally, we present considerations on how CBPR research can be done effectively and ethically, drawing attention to some research gaps.